Susceptibility of Sheep for Scrapie as Assessed by In Vitro Conversion of Nine Naturally Occurring Variants of PrP - Bossers, Alex (American Society for Microbiology, 2000)
Polymorphisms in the prion protein (PrP) gene are associated with phenotypic expression differences of transmissible spongiform encephalopathies in animals and humans. In sheep, at least 10 different mutually exclusive polymorphisms are present in PrP. In this study, we determined the efficiency of the in vitro formation of protease-resistant PrP of nine sheep PrP allelic variants in order to gauge the relative susceptibility of sheep for scrapie. No detectable spontaneous protease-resistant PrP formation occurred under the cell-free conditions used. All nine host-encoded cellular PrP (PrP(C)) variants had distinct conversion efficiencies induced by PrP(Sc) isolated from sheep with three different homozygous PrP genotypes. In general, PrP allelic variants with polymorphisms at either codon 136 (Ala to Val) or codon 141 (Leu to Phe) and phylogenetic wild-type sheep PrP(C) converted with highest efficiency to protease-resistant forms, which indicates a linkage with a high susceptibility of sheep for scrapie. PrP(C) variants with polymorphisms at codons 171 (Gln to Arg), 154 (Arg to His), and to a minor extent 112 (Met to Thr) converted with low efficiency to protease-resistant isoforms. This finding indicates a linkage of these alleles with a reduced susceptibility or resistance for scrapie. In addition, PrP(Sc) with the codon 171 (Gln-to-His) polymorphism is the first variant reported to induce higher conversion efficiencies with heterologous rather than homologous PrP variants. The results of this study strengthen our views on polymorphism barriers and have further implications for scrapie control programs by breeding strategies.